The inclusive economic development model in Sulawesi island - Rudy Badrudin; Manggar Wulan Kusuma; Ranti Yulia Wardani (Economic Journal of Emerging Markets, 2018)
This study aims to determine whether there is an inclusive economic development in Sulawesi Island. Source data used are secondary data from the financial statements of the Local Government regency and city in Sulawesi Island in 2009-2016. The data analysis technique used is the analysis Partial Least Square were tested using samples 9 different areas. The results showed that 1) general allocation fund has positive effect on capital expenditure; 2) own source revenue has positive effect on capital expenditure; 3) capital expenditure has positive effect on economic growth; 4) economic growth has negative effect on welfare of society; and 5) economic growth has negative effect on poverty